[OPPOSITION TO BILL FOR SMOKING RESTRICTION IN FEDERAL BUILDINGS] - SPARBER P # (Tufts Archival Research Center, 2007)
Memorandum from Peter Sparber to Howard Liebengood regarding Senator Stevens’ proposed bill to restrict smoking in all federal buildings. Lists labor unions and veterans groups that have reservations about the restrictions. Emphasizes importance of fighting the bill successfully.